ASSESSMENT OF AWARENESS LEVEL REGARDING RABIES AMONGST SCHOOL STUDENTS IN KANPUR NAGAR - Martollia, D S; Chaudhary, V K; Goel, Pooja; Chandra, Suresh; Verma, Santosh Kumar; Katiyar, Praveen (Indian Journal of Community Health, 2008)
.